Cerebrospinal fluid neurofilament light chains and CXCL13 as predictive factors for clinical course of multiple sclerosis - Hradílek, Pavel; Revendová, Kamila; Horáková, Jana; Bunganic, Radovan; Pelisek, Ondrej; Zeman, David; Hanzlíková, Pavla; Kušnierová, Pavlína (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2023)
AIM: The aim of this study was to identify whether NfL and CXCL13 cerebrospinal fluid (CSF) concentrations at diagnostic lumbar puncture can predict the course of multiple sclerosis (MS) in terms of relapses, higher expanded disability status scale (EDSS) and magnetic resonance imaging (MRI) activity. METHODS: We conducted a single-centre prospective observational cohort study at the MS center, University Hospital Ostrava, Czech Republic. CSF NfL (cNfL) and CXCL13 concentrations were examined (ELISA method) in patients with clinically isolated syndrome (CIS) and relapsing-remitting MS (RRMS) at the time of diagnostic lumbar puncture. RESULTS: A total of 44 patients with CIS or early RRMS were enrolled, 31 (70.5%) of whom were women. The median age at the time of CSF sampling was 31.21 years (IQR 25.43-39.32), and the follow-up period was 54.6 months (IQR 44.03-59.48). In the simple and multiple logistic regression models, CXCL13 levels did not predict relapses, MRI activity or EDSS > 2.5. Similarly, cNfL concentrations did not predict relapses or MRI activity in either model. In the multiple regression, higher cNfL levels were associated with reaching EDSS > 2.5 (odds ratio [OR] 1.002, 95% confidence interval [CI] 1.000 to 1.003). CONCLUSIONS: Our data did not confirm cNfL and/or CXCL13 CSF levels were predictive factors for disease activity such as relapses and MRI activity at the time of diagnostic lumbar puncture in patients with RRMS. While cNfL CSF levels predicted higher disability only after adjustment for other known risk factors, elevated CSF CXCL13 did not predict higher disability at all.
Keywords: dospělí; Recurrence; Female; biologické markery; Biomarkers; Adult; ženské pohlaví; relabující-remitující roztroušená skleróza; Chemokine CXCL13; intermediární filamenta; lidé; Multiple Sclerosis; recidiva; roztroušená skleróza; prospektivní studie; Male; progrese nemoci; Prospective Studies; Multiple Sclerosis, Relapsing-Remitting; Disease Progression; Intermediate Filaments; mužské pohlaví; chemokin CXCL13; Humans